2012
DOI: 10.1099/ijs.0.030825-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus lactis sp. nov., from Italian raw milk cheeses

Abstract: Ten atypical Enterococcus strains were isolated from Italian raw milk cheeses. The 16S rRNA gene, phenylalanyl-tRNA synthase alpha subunit (pheS), RNA polymerase alpha subunit (rpoA) and the 16S-23S rRNA intergenic transcribed spacer (ITS) sequences, randomly amplified polymorphic DNA (RAPD) PCR and the phenotypic properties revealed that the isolates represent a novel enterococcal species. On the basis of 16S rRNA gene sequence analysis, the isolates were closely related to Enterococcus hirae ATCC 8043 T , En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 24 publications
3
48
0
Order By: Relevance
“…Among these colonies, PMD74 was selected for further experiments as it exhibited the highest antimicrobial activity. e characteristic properties (Gram-positive, catalase-negative and aesculin-positive, coccus-shaped isolate that was able to grow effectively at 10-45°C, pH 9.6, and in the presence of both NaCl and bile salts) of the strain were consistent with the general characteristics of genus Enterococcus [17]. According to the results of the API 20 Strep test, the isolate was observed to generate a positive reaction for Voges-Proskauer, pyrrolidonyl arylamidase, and leucine aminopeptidase, while it was negative for α-galactosidase, β-glucuronidase, and hippurate.…”
Section: Isolation and Identification Of E Lactis Pmd74 Strainsupporting
confidence: 68%
See 2 more Smart Citations
“…Among these colonies, PMD74 was selected for further experiments as it exhibited the highest antimicrobial activity. e characteristic properties (Gram-positive, catalase-negative and aesculin-positive, coccus-shaped isolate that was able to grow effectively at 10-45°C, pH 9.6, and in the presence of both NaCl and bile salts) of the strain were consistent with the general characteristics of genus Enterococcus [17]. According to the results of the API 20 Strep test, the isolate was observed to generate a positive reaction for Voges-Proskauer, pyrrolidonyl arylamidase, and leucine aminopeptidase, while it was negative for α-galactosidase, β-glucuronidase, and hippurate.…”
Section: Isolation and Identification Of E Lactis Pmd74 Strainsupporting
confidence: 68%
“…e strain possessed weak acid production ability from starch. e finding that the PMD74 strain did not produce gas from sucrose, while it produced gas from salicin, also supported the proposition that PMD74 was a different strain than E. hirae [17]. According to the complete 16S rRNA gene sequence analysis, which was performed in order to ensure molecular identification, the isolate was designated as an Enterococcus lactis strain.…”
Section: Isolation and Identification Of E Lactis Pmd74 Strainsupporting
confidence: 54%
See 1 more Smart Citation
“…The genus Enterococcus has been the target of several studies for use as probiotics (Sivieri et al 2008;Kuritza et al 2011). They have some desirable characteristics for this purpose such as resistance to gastric juice and bile salts (Rossi et al 2003) and production of antimicrobial compounds such as enterocin (Franz et al 1999;Saarela et al 2000).The genus has been isolated from different niches such as water (Oliveira and Pinhata 2008), plants (Svec et al 2011), animals (Jung et al 2007) and foods (Gomes et al 2008) and different species have been used as starter or adjunct culture in the manufacture of fermented products such as cheese (Centeno et al 1999;Ghairi et al 2008;Williams and Withers 2010;Morandi et al 2011) and sausages (Sabia et al 2002;Tanasupawat et al 2008), among others.Although some studies have corroborated its effectiveness as probiotic (Bellomo et al 1980;Saavedra et al 2001;Benyacoub et al 2003;Rivera-Espinoza and Gallardo-Navarro 2010), others have shown correlation of the genus with diseases, which include urinary tract infections (Protonotariou et al 2010), bacteremia (Shankar et al 1999, Shankar et al 2002Tan et al 2010) and endocarditis (Conde-Estéves et al 2010;Rasmussem et al 2010;Heikens et al 2011). However, the host is usually patients with serious diseases and immuno-compromised (Brilliantova et al 2010) what emphasizes its opportunist nature.…”
Section: Introductionmentioning
confidence: 99%
“…may belong to species Enterococcus lactis, as these isolates were genotypically related to E. faecium. This species, recently proposed for enterococci isolated from different dairy products (Bauer et al 2009;Morandi et al 2011a;Sukhodolets et al 2005), has been recently validated (Morandi et al 2011b).…”
Section: Phenotype Of the Isolatesmentioning
confidence: 99%